Analysis of spatial distribution of sediment toxicity in the 2nd reservoir of the Kis Balaton Water Protection System - Kováts, Nóra; Borbély, Gábor; Magyar, Imre; Szép, Zsuzsanna; Paulovits, Gábor; Pomogyi, Piroska (Acta Agraria Kaposváriensis, 2006)
Prior to 1863 the Kis-Balaton functioned as a natural filter zone, retenting most of the nutrients carried by River Zala. In 1863 by the construction of the Sió sluice control of the water level of Lake Balaton became feasible. As a consequence, marshlands of Kis-Balaton began to disappear and the filtering function started to degrade. Due to these facts water quality of the lake turned into eutrophic by the 1960’s. Main function of the Kis-Balaton Water Protection System is the protection of the water quality of Lake Balaton by retaining most of the nutrients and suspended solids carried by the River Zala and other small watercourses in two reservoirs. Besides this natural cleaning function, however, Kis-Balaton is also a significant nature conservation area under the Ramsar Convention since 1979. Efficiency of the System is continously monitored. However, load presented by diffuse pollution sources such as agricultural runoff cannot be determined. Our goal was to reveal how ecological risk in the stage 2 is determined by external sources, analysing spatial distribution and trends in contamination. For mapping contamination digital ortophoto provided by the Western-Transdanubian Water Authority was used.